Effects of dietary bile acid on the growth performance, intestinal health, blood biochemistry, and antioxidative response of Nile tilapia (Oreochromus niloticus) fed high-fat diets - Mahmoud A.O. Dawood; Sameh El-Dahan; Samy Elsaadawy; Ahmed E. Noreldin; Hani Sewilam (Aquaculture Reports)
High-fat (HF) diets are often used in aquaculture as a nonprotein energy source, resulting in lower feed costs and nitrogen emissions. However, high-fat diets have a deleterious influence on aquatic species' metabolic and immunological functioning. Thereby, bile acid (BA) is proposed to relieve the lipid metabolism dysfunction, oxidative stress, and malnutrition caused by HF. In this study, Nile tilapia (4.97 ± 0.34 g) were distributed in six groups in triplicates and stocked in fifteen 100 L plastic tanks. Fish offered six isonitrogenous test diets for 60 days: the control (6 % fat) without BA (LF) and five HF (12 % fat) diets supplemented with BA at 0, 0.05, 0.1, 0.15, and 0.2 g/kg. The results indicated that the HF diet lowered growth, feed efficiency, and survival rates. Furthermore, the fish-fed high-fat diet demonstrated reduced digestive enzyme activity (lipase and amylase), growth hormone (GH), and antioxidative responses (SOD, CAT, and GPx). The intestine of tilapia-fed HF showed also impaired histomorphological features such as reduced villi length and width. However, supplementation of BA in HF diets improved intestinal and villi architecture. The HF diet without BA supplementation revealed massive hepatic steatosis pancreatic vascular congestion and a high necrotic pancreatic cells number. While supplementing BA in HF diets enhanced pancreatic architecture and decreased necrotic hepatocytes. Fish-fed HF diet also showed increased total cholesterol, triglycerides, glucose, ALP, and AST levels as well as the malondialdehyde level (MDA). On the other hand, fish-fed LF and HF/BA diets showed improved growth performance, lipase and amylase, GH, SOD, CAT, and GPx, and intestinal histo-morphology and reduced glucose, leptin, and MDA levels. Dietary BA at 0.15–0.2 g/kg improved the digestion, and antioxidative capacity. In conclusion, dietary BA is required to mitigate the negative impacts of high-fat diets on Nile tilapia growth performance, general health, and antioxidative response.